Meta-Analisis Implementasi Penguatan Pendidikan Karakter di Sekolah Dasar - Khotimah, Husnul; Hermanto, Hermanto; Mujiono, Mujiono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to evaluate both the successes and weaknesses of the implementation of Character Education Strengthening (Penguatan Pendidikan Karakter/PPK) in elementary schools in building students' character. The research method used is meta-analysis through a systematic literature review. This method was chosen because the primary studies reviewed in this research employed a qualitative approach. The study concludes that: (1) PPK is clearly defined in terms of its legal basis, concepts, objectives, and implementation strategies; (2) teachers and education personnel in elementary schools tend to have a limited understanding of the concept and implementation strategies of PPK; (3) elementary schools' readiness to implement PPK is generally still at the planning stage; and (4) the implementation of PPK has not yet produced the expected outcomes. Recommendations based on the findings of this meta-analysis Keywords: Character Education Strengthening, Implementation, Teachers And Education Personnel